Guru Agama Islam sebagai Pilar Pembentukan Akhlak Siswa di Madrasah Nahdhatul Islamiah Krasak, Thailand Selatan - Seena, Isamaae; Rahmat; Ratna, Rizky dwi (Universitas KH. Abdul Chalim Pacet Mojokerto, 2023)
This study investigates the moral condition of students, identifies the factors influencing their moral development, and examines the role of Islamic religious teachers in nurturing these morals at Madrasah Nahdhatul Islamiah Krasak. Employing a qualitative case study approach, the research involves observation, in-depth interviews, and documentation. To ensure the validity of the findings, the study uses observer persistence and triangulation. The findings reveal several key insights. The moral condition of students at the Madrasah reflects ongoing efforts to cultivate noble character. Teachers are expected to prepare detailed lesson plans and utilize lecture methods and advisory discussions to convey the importance of key moral teachings. Each religious teacher must be well-versed in the Madrasah’s curriculum and have a comprehensive plan for imparting these lessons to their students. Support for fostering student morals comes from several sources. Role modeling by teachers, active involvement from parents, and the availability of Madrasah facilities are identified as significant supporting factors. Conversely, challenges such as the influence of online games, varying student backgrounds, and peer pressure pose obstacles to moral development. The role of Islamic religious teachers is pivotal in creating a conducive learning environment. They are tasked with ensuring that the classroom is safe, clean, aesthetically pleasing, and well-organized. Additionally, teachers are responsible for greeting students, preparing teaching materials in advance, and providing guidance and advice. These efforts are designed to create a positive and calm learning atmosphere aimed at instilling a deep awareness of Islamic values and nurturing noble character among students.